Research on the performance and causes of the company’s abusive leadership - Taking "A" company in China as example - Dai, Yuxin (2019)
As a negative leadership behavior, abusive leadership has gradually attracted the attention of scholars and business managers. It not only harms the benefits of employees and enterprises but also has negative effects on the development of the social economy. Among the existing studies, the research on the phenomenon of abusive leadership is mostly focused on enterprises in Western countries, while the research on Chinese enterprises is rare. To make up for this deficiency in existing research, the researcher decides to explore the specific performance and causes of abusive leadership in a Chinese company. So as to lay a foundation for Chinese enterprises to reduce and eliminate this kind of leadership behavior in the future. The researcher chooses employees in a Chinese company called “A” as a research sample. According to her research results, she finds the abusive leadership exists in this company. And the results of the study on the causes of abusive leadership coincide with the preliminary expectation of the researcher. These four causes are: organizational factors, work factors, supervisor factors, and subordinate factors. The researcher also finds the most frequently mentioned factors by interviewees is the supervisor factors. The findings of this study can be used as a reference for future scholars who want to study this topic. Moreover, “A” Company and other similar enterprises in China can directly formulate corresponding solutions to reduce the conflict between managers and employees according to the causes of abusive leadership summarized in this study.